Respuesta :
Answer:
[tex]5^{-2}[/tex]
Step-by-step explanation:
Using the rule of exponents
[tex]a^{-m}[/tex] ⇔ [tex]\frac{1}{a^{m} }[/tex] , then
[tex]\frac{1}{25}[/tex] = [tex]\frac{1}{5^{2} }[/tex] = [tex]5^{-2}[/tex]
In exponent form, it should be written as [tex]5^{-2}[/tex].
Given that,
- The fraction is [tex]\frac{1}{25}[/tex]
- We need to write in the exponent form
Based on the above information, the calculation is as follows:
[tex]a^{-m} = \frac{1}{a^{m}} \\\\\frac{1}{25} = \frac{1}{5^{2}}[/tex]
[tex]5^{-2}[/tex]
Learn more: brainly.com/question/17429689